Biomass production in whey permeate and spray drying of a potential probiotic strain from human breast milk, Bifidobacterium animalis subsp. lactis INL1 - Zacarias, Maria Florencia (2025)
Whey permeate (WP), a by-product of cheese whey treatment, constitutes a sustainable and economical alternative to synthetic media for probiotic biomass production. Likewise, spray drying (SD) is a rapid and cost-effective alternative to freeze drying in industrial practice. This study aimed to optimise the production of a spray-dried culture (SDC) of Bifidobacterium animalis subsp. lactis INL1. Biomass production on WP was optimised by analyzing the effects of yeast extract and pH on bacterial growth, survival during spray drying, and resistance to simulated gastric digestion. Additionally, pH, inlet temperature, and drying matrix effects were evaluated for their impact on strain resistance during SD and storage. WP proved to be a suitable ingredient for B. lactis INL1 biomass production. Acidic culture conditions yielded superior results, and all tested factors significantly influenced SDC performance. These findings highlight the usefulness of optimization strategies to define effective production conditions for probiotic cultures.